Charley Patton between Sacral and Profane - Weber, Jane (Traditiones, 2019)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"><span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The article introduces Charley Patton’s religious songs on 78 rpm gramophone records recorded in the period from 1929 to 1934. Almost all of Patton’s varied musical skills come out on those records. For example, the power of his music is often most evident in his spiritual and gospel work. The author writes about the divide between secular and sacred music in Afro-American culture and particularly in Patton’s legacy. The author was also mainly interested in crossing of that dividing line and in blending of various styles, and he ascertained that in his performances Patton easily crossed the line of separation between sacred and profane.